2016
DOI: 10.1214/15-aop1022
|View full text |Cite
|
Sign up to set email alerts
|

Large complex correlated Wishart matrices: Fluctuations and asymptotic independence at the edges

Abstract: We study the asymptotic behavior of eigenvalues of large complex correlated Wishart matrices at the edges of the limiting spectrum. In this setting, the support of the limiting eigenvalue distribution may have several connected components. Under mild conditions for the population matrices, we show that for every generic positive edge of that support, there exists an extremal eigenvalue which converges almost surely toward that edge and fluctuates according to the Tracy-Widom law at the scale N 2/3 . Moreover, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(81 citation statements)
references
References 74 publications
3
78
0
Order By: Relevance
“…β n K n ((u n , r n ), (v n , s n )) =        J n − Φ n ; for cases (1-4), J n + Φ n ; for cases (5,6), −J n − Φ n ; for cases (7,8), −J n + Φ n ; for cases (9-12), where we define: ; for cases (9)(10)(11)(12).…”
Section: The Main Results Of This Section Is Thenmentioning
confidence: 99%
See 3 more Smart Citations
“…β n K n ((u n , r n ), (v n , s n )) =        J n − Φ n ; for cases (1-4), J n + Φ n ; for cases (5,6), −J n − Φ n ; for cases (7,8), −J n + Φ n ; for cases (9-12), where we define: ; for cases (9)(10)(11)(12).…”
Section: The Main Results Of This Section Is Thenmentioning
confidence: 99%
“…(ii) {y ∈S 1,n ∪S 3,n : y ∈ Γ • n } equalsS 1,n for (1-6), and equalsS 3,n for (7-12). (iii) {y ∈ (S 1,n ∪S 3,n ) ∩ V n : y ∈ γ • n ∩ Γ • n } equals (V U (n) ) ∩ P n for (1-3) and (6) when v n ≥ u n , equals (V U (n) ) ∩ P n for (7) and (10)(11)(12) when v n + s n ≤ u n + r n , and is empty otherwise. (iv) {y ∈ V n \ U n : y ∈ γ • 2,n } equals V U (n) for (6) when v n ≥ u n , equals V U (n) for (7) when v n + s n ≤ u n + r n , is empty for (6) when u n > v n , and is empty for (7) when v n + s n > u n + r n .…”
Section: The Main Results Of This Section Is Thenmentioning
confidence: 99%
See 2 more Smart Citations
“…See Hachem et al . () and Lee and Schnelli () for recent results. In Gaussian white noise, Johnstone () showed that the scale parameter isτp=n1/2false{1+false(pfalse/nfalse)1false/2false}{n1/2+p1/2}1/3,so fluctuations in the largest eigenvalue quickly become negligible.…”
Section: Introductionmentioning
confidence: 94%